Intelligent computer mathematics : 10th International Conference, CICM 2017, Edinburgh, UK, July 17-21, 2017, Proceedings /: 10th International Conference, CICM 2017, Edinburgh, UK, July 17-21, 2017, Proceedings. (2017) - Unknown
No abstract available